Evaluation of Processing Methods for Formulated Tablets of Loranthus micranthus (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Loranthus micranthus is one of the many plants that has documented evidence of safety and efficacy in the management of many ailments and widespread use in almost every part of Nigeria. It is desirable to formulate it into a suitable dosage form for use by the populace.Objectives: The research was aimed at formulating the aqueous leaf extract of L. micranthus into a tablet dosage form by wet granulation and direct compression methods.Methods: For wet granulation method, maize starch, gelatin, polyvinyl pyrrolidone and acacia were used as binders for the formulations each was used at 2, 3, 4 and 5 % w/w concentration in the tablet. The direct compression method involved the preparation of an extract containing material (ECM). Microcrystalline cellulose, pregelatnised starch, starlac and spray dried lactose were used as filler binders for the direct compression. All the formulated tablets were assessed by comparing the crushing strength-friability ratio (CSFR) and the disintegration time (DT) to select an optimum formulation that meets both mechanical and release properties.Results: Using wet granulation method, maize starch and gelatin (at 3 %w/w) binder concentration as well as gelatin at 2 %w/w binder concentration produced the optimal formulations. The tablets formulated by direct compression all disintegrated within 10 min and below with microcrystalline cellulose (MCC) tablets disintegrating at 7 min. In dissolution studies, all the optimized formulations released more than 70 % of the extract within 40 min with MCC releasing up to 98 % in 30 min.Conclusion- Direct compression of the extract containing material produced improved tablet formulations than the wet granulation method.